Design of software code to improve the accuracy of shrimp grading machine - Chan, Chao Shiung (2016)
Shrimp is a famous dish all around the world, it is famous with its taste and variety of dish be match with shrimps. In the pass, it is possible to grade shrimp manually using manpower as peoples are not aware of the juicy taste of shrimp. By using manual shrimp grading, people often creates human error and did some mistakes in grading shrimp when it comes to mismatching the size with the standard grading parameter. To grade food, it requires precise accuracy on differentiating the weight of the food as every grams of the food comes with price depending on how much weight it produces and types of food being grade. All the while, beside manual shrimp grading by manpower, there are other method such as grading shrimp mechanically and image processing been used. This project uses weight sensor to grade shrimp because it suits the needs of buyers and the market. By using weight sensor, it is faster then the image processing method because the sensor is placed under the conveyor to measure the product such as shrimp once the shrimp goes on top of it. Weight sensor also produces less error when it does not depends on external source such as light to operates, the only limitation for weight sensor is the range of weight prefered by the factory to grade shrimp. The main objective of this project is to create a software code using MATLAB and C programming so that it could help improve the shrimp grading accuracy interms of quality, cost effectiveness, and man power.